Choosing friends based on similarity or popularity? Friendship preferences of children exhibiting bullying and defending in late childhood - Liu, Xiaowei; Pan, Bin; Salmivalli, Christina; Zhang, Wenxin; Ji, Linqin (SAGE Publications, 2026)
This study examined whether children with high levels of bullying or defending rather choose similar or popular peers as friends in late childhood. We expected that friendship preferences of children were based on similarity in bullying and defending behaviors. Moreover, we assumed that children's bullying behavior was associated with the tendency to seek out popular peers as friends. To test these hypotheses, we analyzed data from third- (Mage = 9.35 years) and fourth-grade (Mage = 10.46 years) students in China (N = 453, 54.79% boys at wave 1; N = 454, 54.35% boys at wave 2; N = 453, 54.05% boys at wave 3). Longitudinal social network analysis revealed that children's level of bullying behavior was associated with their likelihood of choosing popular peers as friends, while defending behavior was related to a tendency to select peers with similar levels of defending as friends. The study sheds light on "whom" children with bullying or defending behaviors select for affiliation within Chinese culture, and has implications for prevention and intervention of school bullying.